Identifying Incident Cancer Cases in Medicine Dispensing Claims: A Validation Study Using Australia’s Pharmaceutical Scheme (PBS) Data - Benjamin Daniels; Hanna E Tervonen; Sallie-Anne Pearson (International Journal of Population Data Science, 2020)
Introduction Dispensing claims are used commonly as proxy measures in pharmacoepidemiological studies, however, their validity is often untested.